Investasi dan Konservasi di Danau Perintis Kecamatan Suwawa Kabupaten Bone Bolango - Rahmawati A. Damiti; Dewi Wahyuni K. Baderan; Marini Susanti Hamidun (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
The Perintis Lake area in Bone Bolango Regency, Gorontalo Province, faces a growing conflict between tourism investment and environmental conservation. This study aims to analyze the impact of tourism infrastructure development on the lake’s ecosystem, highlight the importance of conservation, and provide strategic recommendations for sustainable tourism development. Using a qualitative-descriptive approach, the research is based on field observations, literature review, and regional policy analysis. Findings show that unregulated investment activities, particularly constructions along the lake's buffer zone, have led to environmental degradation, such as water pollution, habitat loss, and ecological imbalance. Conservation efforts remain fragmented and lack integration into broader development planning. The study recommends the implementation of sustainable spatial planning policies, stricter environmental regulations, and active community involvement. Collaborative governance between local authorities, private investors, and environmental stakeholders is essential to ensure that economic development aligns with ecological preservation. Striking a balance between investment and conservation is key to maintaining Perintis Lake as a resilient ecotourism destination for future generations.